PENGARUH UKURAN PERUSAHAAN, LIKUIDITAS, DAN KEBIJAKAN DIVIDENTERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Sektor Consumer Non Cyclicals Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023) - Ningrum, Mega Puspa; Mulyadi, Mulyadi; Rossa, Elia (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to analyze and examine the influence of company size, liquidity, and dividend policy on firm value. This research employs quantitative methods. The data sources used are secondary data, consisting of annual financial reports of companies listed on the Indonesia Stock Exchange for the years 2019-2023. The sampling technique used purposive sampling, resulting in 120 observational data samples. Data processing in this study used IBM SPSS (Statistical Product and Service Solution) version 26 software. The results of this study indicate that company size does not significantly influence firm value, liquidity significantly influences firm value, and dividend policy significantly influences firm value.